Эффект расширения костных каналов после реконструкции передней крестообразной связки - Красноперов, С. Н.; Головаха, М. Л.; Krasnoperov, S. N.; Golovaha, M. L.; Краснопьоров, Сергій Миколайович; Головаха, Максим Леонідович (Ин-т патологии позвоночника и суставов им. проф. М. И. Ситенко НАМН Украины, 2018)
Для реконструкции передней крестообразной связки (ПКС) в ортопедии и травматологии используют различные пластические материалы и значительное количество методов фиксации трансплантата в бедренной и большеберцовой костях [1, 2]. Известны различные виды осложнений после восстановления ПКС, одним из которых является расширение костных каналов в послеоперационном периоде [3]. Цель работы: оценить расширение костных каналов после реконструкции передней крестообразной связки на основе компьютерной томографии. One of the complications after anterior cruciate ligament reconstruction is widening of bone canals after surgery, it can lead to slow integration of the graft with bone, promotion of secondary instability and revision reconstruction of anterior cruciate ligament. In order to fix the graft in the femoral and tibia bones endobuttons and interferent screws are widely used. Objective: to evaluate the widening of bone canals after anterior cruciate ligament reconstruction due to computer tomography. Methods: there were 44 patients, who were divided into: group A (24) — technique «all inside» w ith fi xing o f s emitendinosus g raft with short cortical endobutton in the femur and tibia; group B (20) — fixing of semitendinosus and gracilis graft with interferent screws (transportal technique). The rehabilitation protocol was the same for both groups. The mid term for computer tomography study was 10 months after surgery. Results: in group A the average widening of bone canal diameter in the femur was 15 % in the entrance, 12 % in the middle part as to the primary size. In group B — 10 and 7 % respectively. The diameter of the tibia canal enlarged in average: in group A 19 % in the entrance, 15 % in the middle part; in group B — 15 and 11 % respectively. According to clinical study there was not significant difference between groups. Conclusions: in the group where we used cortical fixators the widening of the canals was larger than in those where we used interferent screws, but the difference was not significant, only 5 % for femoral side and 4 % for tibia canals. X-ray signs of canal widening did not influence on clinical or objective results of anterior cruciate ligament reconstruction. Одним із ускладнень після відновлення передньої схрещеної зв’язки (ПСЗ) є розширення кісткових каналів у післяопераційному періоді, яке може призвести до уповільненої інтеграції трансплантата з кістковою тканиною, розвитку вторинної нестабільності та ревізійної реконструкції ПСЗ. Найчастіше для закріплення трансплантата в стегновій і великогомілковій кістках використовують гудзикові підвісні фіксатори (Endobutton) та інтерферентні гвинти. Мета: оцінити розширення кісткових каналів після реконструкції ПСЗ на підставі комп’ютерної томографії (КТ). Висновки: у групі, де використовували кортикальні фіксатори розширення каналів виявилося більшим, ніж у випадку застосування інтерферентних гвинтів, але різниця цього збільшення між групами незначна — лише 5 % для стегнового та 4 % для великогомілкового каналів. Рентгенологічні показники розширення кісткових каналів не впливали на клінічні суб’єктивні й об’єктивні результати реконструкції ПСЗ.
Effect of bone canal widening after anterior cruciate ligament reconstruction
Keywords: реконструкция передней крестообразной связки; расширение костных каналов; компьютерная томография; anterior cruciate ligament reconstruction; widening of bone canals; computer tomography; реконструкція передньої схрещеної зв’язки; розширення кісткових каналів; комп’ютерна томографія